2021
DOI: 10.3390/jmse9010086
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Destructive and Constructive Morphodynamic Processes in Steep Beaches

Abstract: Short-term beach morphodynamics are typically modelled solely through storm-induced erosion, disregarding post-storm recovery. Yet, the full cycle of beach profile response is critical to simulating and understanding morphodynamics over longer temporal scales. The XBeach model is calibrated using topographic profiles from a reflective beach (Faro Beach, in S. Portugal) during and after the incidence of a fierce storm (Emma) that impacted the area in early 2018. Recovery in all three profiles showed rapid steep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…tidal range, wave climate, and sediment availability) were considered to be stationary. It is also important to highlight that the beach width mapping was performed on images from the end of the spring season, suggesting that the berm could already have reached its maximum robustness, given the fact that beach recovery is very fast in the study area (Kombiadou et al, 2021; Malvarez et al, 2021). Thus, berm robustness or backshore volume was computed as the product of the backshore width (measured from the satellite images as the distance between the wet/dry and the vegetation lines) and the berm height (constant within each sector).…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…tidal range, wave climate, and sediment availability) were considered to be stationary. It is also important to highlight that the beach width mapping was performed on images from the end of the spring season, suggesting that the berm could already have reached its maximum robustness, given the fact that beach recovery is very fast in the study area (Kombiadou et al, 2021; Malvarez et al, 2021). Thus, berm robustness or backshore volume was computed as the product of the backshore width (measured from the satellite images as the distance between the wet/dry and the vegetation lines) and the berm height (constant within each sector).…”
Section: Methods and Datamentioning
confidence: 99%
“…tidal range, wave climate, and sediment availability) were considered to be stationary. It is also important to highlight that the beach width mapping was performed on images from the end of the spring season, suggesting that the berm could already have reached its maximum robustness, given the fact that beach recovery is very fast in the study area (Kombiadou et al, 2021;Malvarez et al, 2021).…”
Section: Estimation Of Dune Retreat and Abiotic And Biotic Factorsmentioning
confidence: 99%
“…9 and 12). As the present work only focused on destructive processes induced by storms, these settings might not be appropriate to simulate constructive morphological processes in the long term, as found by Kombiadou et al (2021). The comparison between the 1D and 2D hydrodynamic and morphological outputs for the high-energy Storm Emma demonstrated that the higher erosion simulated by the 1D model was related to the higher infragravity wave height simulated in the 1D model (Fig.…”
Section: D Modelmentioning
confidence: 86%
“…(Cohn et al 2019a). Although aeolian transport plays a minor role relative to the wave-driven processes in storms, even during the recovery phase (e.g., Kombiadou et al 2021), the inclusion of these processes will improve simulations on timescales of years to decades. The effects of wave growth due to local winds can also be included.…”
Section: Community and Open-source Modelsmentioning
confidence: 99%